Current Situation Detection and Performance Evaluation Analysis of Existing Double-curved arch bridge. Issue 5 (February 2020) - Zhou, Yongjun; Wang, Gangqiang; Cao, Xiaozhe; Tian, Ruixin
Abstract: The existing design load level of the existing double-curved arch bridge is generally low, the old-fashioned inferiority and the poor overall integrity, which are likely to cause structural damage and affect the normal use of such structures. Based on the appearance inspection and static and dynamic load test of a dangerous three span double-curved arch bridge without original design data, this paper discusses the methods of structural modeling, load test and structural performance evaluation of this kind of bridge, which provides reference to the current situation evaluation of similar bridges. Through the inspection of bridge appearance defects, component cracks, deformation displacement, steel protective layer thickness, concrete carbonization depth and material strength, combined with the load test results, the comprehensive technical status of the bridge is determined to be 4 types of bridges. The bearing capacity meets the requirements of load grade Automobile-10 class, but the safety reserve is insufficient.